Mrs. Piggle-Wiggle's magic - MacDonald, Betty Bard.; Knight, Hilary (New York : Scholastic Inc., 1987)
Seven families are helped out by Mrs. Piggle-Wiggle's magic cures when they are faced with thought-you-saiders, tattletales, bad table manners, interrupters, heedless breakers, never-want-to-go-to-schoolers, and wadde-I-doers.
G12
Keywords: Fantasy; Humorous stories